Increasing Female Enrollment for Agricultural Programs of Study in Sub-Saharan Africa: What Motivates Women to Pursue Careers in Agriculture? - Stephen C. Mukembo; José M. Uscanga; Craig M. Edwards; Nicholas R. Brown (Journal of International Agricultural and Extension Education, 2017)
Women in developing countries, especially in Sub Saharan Africa (SSA), play a critical role in ensuring food security and sovereignty for their families and nations. Unfortunately, in spite of this, their significance in the agricultural sector is seldom fully appreciated. Further, very few women in SSA are professionally trained agriculturists (Beintema & Di Marcantonio, 2009; Kanté, Edwards, & Blackwell, 2013), which has likely contributed to their low productivity per hectare in the agricultural sector compared to their male counterparts (O'Sullivan, Rao, Banerjee, Gulati, & Vinez, 2014). This study investigated the experiences of young, aspiring female agriculturists from Uganda who were members of Young Farmers’ Clubs (YFC) at high school to understand better how their club experiences may have impacted their career choices. Findings indicate the participants’ YFC activities, especially supervised agripreneurship projects (SAPs) and field trips, had transformative impacts on their choosing to study agriculture. However, gender stereotypes associated with females pursuing agricultural careers were still prevalent and discouraged them from becoming professional agriculturists. More research should be conducted about the impact of subjective norms (Ajzen, 1991) on females preparing to pursue careers in agriculture
Keywords: careers; female agriculturists; Sub-Saharan Africa; Young Farmers’ Clubs